ФИЗИЧЕСКАЯ КУЛЬТУРА КАК ФАКТОР ВАЛЕОЛОГИЧЕСКОГО И ЭКОЛОГИЧЕСКОГО ВОСПИТАНИЯ СТУДЕНТОВ - Абдукаримов, Н.А. (SCIENCE and SOCIETY, 2021)
This article defines, the main categories and concepts that allow to present the ecological education of students in the perspective of physical culture of' the individual. The functions examined allow the student to master various technologies of ecological and physical education of the person, which ensure the formation of ecological consciousness and ecological culture.
Keywords: physical culture; ecology; valeology; healthy student; personality; nature; specialist; ecological content